Morphological Marking Irregularity of Bahasa Indonesia and the Acquisition of English Words - Bambang Agus Darwanto; Pratomo Widodo; Hesthi Heru Satoto (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
Abstract: All languages share the same lexical categories such as verb, noun, adjective, and adverb. Unlike English, however, Bahasa Indonesia carries fewer consistent patterns of morphological markers for word categories. A verb, for instance, is marked with the prefix {me-} as in me-nginjak (to step on); however, other verbs do not carry this marker as in makan (eat), tidur (sleep), and tergantung (depend). As for English, the suffix {-ing} or {-ed/-en}, for instance, indicates that the root is a verb regardless of the verb transitivity. This research investigated if the irregularity in the morphological marking of Bahasa Indonesia verbs created problems in acquiring English words. A test of the "word category assignment" (Test 1) was provided to two groups of respondents: undergraduate students of English and doctoral students of Bahasa Indonesia. A "word-in-context translation into English" (Test 2) was given to a group of undergraduates of English. The first was to know if the respondents managed to assign the Bahasa Indonesia words with correct lexical categories, and the second was to know if the words were assigned with correct word categories when translated in English. This was to know if the Bahasa Indonesia and English words received the same word-category. The results show that errors in the assignment of the grammatical categories of the Bahasa Indonesia words were found pervasive among the two groups. And the lexico-grammar behavior seems to give impact on the categorization of the Bahasa Indonesia words when provided in English as also detected in the translation. It is strongly indicative that confusion in the word category assignment of Bahasa Indonesia gives impact on the acquisition of English words.Key words: morphological markers, suffix, word category, language transfer, lexico-grammarAbstrak: Semua bahasa memiliki kategori leksikal yang sama seperti verba, nomina, adjektiva, dan adverbia. Tidak seperti bahasa Inggris, Bahasa Indonesia memiliki pola penanda morfologi yang lebih sedikit untuk kategori kata. Kata kerja, misalnya, ditandai dengan awalan {me} seperti pada me-nginjak; namun verba lain tidak memiliki penanda ini seperti pada makan, tidur, dan tergantung. Sedangkan bahasa Inggris, misalnya sufiks {-ing} atau {-ed /-en}, akar kata (root) adalah kata kerja terlepas dari kata kerja transitivitas. Penelitian ini mencari tahu apakah ketidakteraturan dalam penandaan morfologi kata kerja Bahasa Indonesia menimbulkan masalah dalam mempelajari kata dalam bahasa Inggris. Tes "tugas kategori kata" (Tes 1) diberikan kepada dua kelompok responden: mahasiswa sarjana Bahasa Inggris dan mahasiswa doktoral Bahasa Indonesia. Tes "terjemahan kata-dalam-konteks ke dalam bahasa Inggris" (Tes 2) diberikan kepada sekelompok mahasiswa dari kelompok bahasa Inggris. Tes pertama untuk mengetahui apakah responden berhasil menentukan kata-kata dalam Bahasa Indonesia dengan kategori leksikal yang benar, dan tes kedua untuk mengetahui apakah kata-kata tersebut diberi kategori kata yang benar ketika diterjemahkan ke dalam bahasa Inggris. Tujuan kedua tes tersebut untuk mengetahui apakah kata-kata dalam Bahasa Indonesia dan Bahasa Inggris memiliki kategori kata yang sama. Hasil penelitian menunjukkan bahwa kesalahan dalam pengkategorian gramatikal kata-kata Bahasa Indonesia ditemukan di kedua kelompok. Perilaku lexico-grammar berdampak pada kategorisasi kata-kata dalam Bahasa Indonesia jika diberikan dalam bahasa Inggris seperti yang ditemukan dalam terjemahan. Hal ini menjadi indikasi kuat bahwa kebingungan dalam penetapan kategori kata dalam Bahasa Indonesia berdampak pada pembelajaran kata dalam bahasa Inggris.Kata kunci: penanda morfologi, sufiks, kategori kata, transfer bahasa, lexico-grammar